2013
DOI: 10.1259/bjr.20130190
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of combined18F-FDG PET/CT scan for differential diagnosis between benign and malignant adrenal enlargement

Abstract: Objective: To assess the properties of adrenal lesions with and without known primary cancer and investigate predictors for differential diagnosis between benign and malignant adrenal enlargement. Methods: This retrospective study used fluorine-18 fludeoxyglucose positron emission tomography (PET)/CT in 325 patients with adrenal lesions (229 with known primary cancer and 96 without primary cancer). Age, sex, the presence of right and left masses, nodules or hyperplasia, unenhanced attenuation, maximum standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…From our analysis, patients with primary lung malignancy had almost 11 times greater chance of harboring an adrenal metastasis than those with non-lung primary malignancy. This is consistent with the finding that lung primary malignancy is the most common malignancy metastasizing to the adrenals [1][2][3][10][11] . Using an optimal cut-off of 2.65, those with SUVmax >2.65 had a 31.6 times greater chance of adrenal metastasis than those with SUVmax ≤2.65.…”
Section: Discussionsupporting
confidence: 92%
“…From our analysis, patients with primary lung malignancy had almost 11 times greater chance of harboring an adrenal metastasis than those with non-lung primary malignancy. This is consistent with the finding that lung primary malignancy is the most common malignancy metastasizing to the adrenals [1][2][3][10][11] . Using an optimal cut-off of 2.65, those with SUVmax >2.65 had a 31.6 times greater chance of adrenal metastasis than those with SUVmax ≤2.65.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we have showed that the improvement of signal measurement in dPET leads to an improved physiological uptake in PG. Of course, physiological uptake of other small normal structures (as adrenal glands, ganglia), will be impacted similarly 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The left adrenal gland is the more common site of adrenal metastasis [15,17] and is almost always accessible from the stomach [18,19,20]. Several studies have looked at the use of esophageal ultrasound-guided FNA for the diagnosis of left adrenal lesions [18,19,20].…”
Section: Discussionmentioning
confidence: 99%